Mechanisms of calcium ion inhibiting alkaline fermentation of waste activated sludge for short-chain fatty acids production - Wu, Ruixin; Luo, Jinghuan; Chen, Shanping; Liu, Jianyong; Zhang, Ruina; Li, Yu-You (Environmental technology & innovation, 2022)
Alkaline fermentation is an effective way for short-chain fatty acids recovery from waste activated sludge. However, there is always a high content of calcium ions in waste activated sludge, which may inhibit alkaline fermentation resulting in a low short-chain fatty acids production. The inhibition effect and mechanisms of calcium ions on short-chain fatty acids production from waste activated sludge was investigated and studied in this work. The results showed that when the calcium ions concentration increased from 0 to 5000 mg/L, the short-chain fatty acids production decreased from 307.8 ± 0.7 to 226.8 ± 1.1 mg chemical oxygen demand/g volatile suspended solid. Mechanism study revealed that about 2-fold extracellular polymeric substances were secreted with 5000 mg/L calcium ions addition than that of calcium ions absence to resist the toxic effect of calcium ions, thus inhibiting waste activated sludge disintegration, and less organic substrate were released for the short-chain fatty acids production. Furthermore, flocculation of calcium ions and short-chain fatty acids reduced the short-chain fatty acids concentration in fermentation liquid. [Display omitted] •5000 mg/L calcium inhibited fermentation with 26.3% reduction of SCFAs production.•Aggregation effect of calcium on sludge resulting in the fermentation inhibition.•Complexation of EPS with calcium caused 2-fold EPS remaining in sludge cells.•Flocculation effect of calcium results in SCFAs in liquid lower than expected.